2013
DOI: 10.1371/journal.pone.0061161
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Molecular Characterization of Staphylococcus hominis Isolates from Blood

Abstract: BackgroundAmong Coagulase-Negative Staphylococci (CoNS), Staphylococcus hominis represents the third most common organism recoverable from the blood of immunocompromised patients. The aim of this study was to characterize biofilm formation, antibiotic resistance, define the SCCmec (Staphylococcal Chromosomal Cassette mec) type, and genetic relatedness of clinical S. hominis isolates.Methodology S. hominis blood isolates (n = 21) were screened for biofilm formation using crystal violet staining. Methicillin res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 32 publications
5
33
1
1
Order By: Relevance
“…In a Norway study that worked on cattle and goats, smr was detected in one of two S. hominis isolates, which is higher than our results in humans 24 . With regards to biofilm production, our results were similar to those obtained in certain studies conducted in Argentina and Mexico 25,26 ; however, they contrasted with that of a different Mexico study 4 , which reported high biofilm production in most strains Therefore, the low and moderate biofilm production may be related to factors other than the presence of ica. Given that different ACME types help to maintain S. epidermidis in the environment, the presence of ACME type II in some of these strains may improve their ability to remain and colonize.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In a Norway study that worked on cattle and goats, smr was detected in one of two S. hominis isolates, which is higher than our results in humans 24 . With regards to biofilm production, our results were similar to those obtained in certain studies conducted in Argentina and Mexico 25,26 ; however, they contrasted with that of a different Mexico study 4 , which reported high biofilm production in most strains Therefore, the low and moderate biofilm production may be related to factors other than the presence of ica. Given that different ACME types help to maintain S. epidermidis in the environment, the presence of ACME type II in some of these strains may improve their ability to remain and colonize.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, the methicillin resistance rate was slightly higher than that reported in other studies conducted in the USA (80-82%), Mexico (81%), and Tunis (75%) [2][3][4]18 , and the MDR rate was higher than that reported in the Tunis study (94%) 2 . The different MRSHo rates in different countries may reflect differences in the doses and dosing schedules used and in the spread of particular clones.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Bakteri ini dapat mengakibatkan infeksi pada pasien dengan sistem imun yang lemah. 5 Cara pengambilan yang tidak tepat yang mengakibatkan tercemarnya spesimen kultur dengan kuman komensal kulit dapat menjadi alasan banyak ditemukannya bakteri ini di unit kami.…”
Section: Pembahasanunclassified
“…Staphylococcus haemolyticus and Staphylococcus hominis belong to coagulase-negative staphylococci (6, 7). S. hominis IIF4SC-B9 was resistant to penicillin and erythromycin, but S. haemolyticus IIF2SW-P5 was susceptible to these antibiotics.…”
Section: Genome Announcementmentioning
confidence: 99%